Regulation of chondrogenesis and chondrocyte differentiation by stress - Zuscik, Michael J. (American Society for Clinical Investigation, 2008)
Chondrogenesis and endochondral ossification are the cartilage differentiation processes that lead to skeletal formation and growth in the developing vertebrate as well as skeletal repair in the adult. The exquisite regulation of these processes, both in normal development and in pathologic situations, is impacted by a number of different types of stress. These include normal stressors such as mechanical loading and hypoxia as well pathologic stressors such as injury and/or inflammation and environmental toxins. This article provides an overview of the processes of chondrogenesis and endochondral ossification and their control at the molecular level. A summary of the influence of the most well-understood normal and pathologic stressors on the differentiation program is also presented.